STUDENT TEACHER’S EXPERIENCES OF SPIRITUAL FORMATION AND DIGITAL LEARNING IN A CHRISTIAN HIGHER EDUCATION - Nainggolan, Cathryne Berliana; Ma, Daniel Santoso (Universitas Pelita Harapan, 2022)
The main purpose of Christian higher education is to provide a holistic development of students, including spirituality. In order to enhance student’s spiritual growth, a Christian private university has been developing a comprehensive approach to educational practices regarding the integration of faith and learning. However, the pandemic COVID-19 has been limiting student’s opportunity to experience those practices. The aim of this phenomenological study was to explore the student teachers’ experiences of spiritual formation and digital learning in a Christian Teachers’ College. The number of participants was 20 and data were collected by conducting interviews and self-reflection reports. The findings were classified in three main themes: personal attachment, support network, and diverse learning applications. The findings and implications are expected to reinforce digital learning in Christian higher education in promoting student’s spiritual formation. Bahasa Indonesia AbstrakTujuan utama dari pendidikan tinggi Kristen adalah menyediakan perkembangan naradidik secara holistik, termasuk spiritualitas. Demi meningkatkan pertumbuhan spiritual naradidik, sebuah universitas Kristen telah mengembangkan sebuah pendekatan pendidikan yang komprehensif secara khusus mengenai integrasi antara iman dan ilmu. Akan tetapi, pandemic COVID-19 telah membatasi kesempatan naradidik untuk mengalami praktik-praktik pendidikan tersebut. Tujuan studi fenomenologi ini adalah untuk mengeksplorasi pengalaman mahasiswa guru tentang formasi spiritualitas dan pembelajaran digital di sebuah fakultas keguruan Kristen. Partisipan berjumlah 20 orang dan data diperoleh melalui wawancara dan laporan jurnal refleksi pribadi. Hasil penelitian diklasifikasikan dalam tiga tema utama: keterikatan pribadi (personal attachment), jaringan pendukung (support network), dan penerapan variasi pembelajaran (diverse learning applications). Hasil penelitian dan implikasi diharapkan dapat memperkuat pembelajaran digital serta mendukung formasi spiritualitas nara didik di pendidikan tinggi Kristen.